Society for Immunotherapy of Cancer (SITC) clinical practice guideline on immune checkpoint inhibitor-related adverse events. Issue 6 (25th June 2021) - Brahmer, Julie R; Abu-Sbeih, Hamzah; Ascierto, Paolo Antonio; Brufsky, Jill; Cappelli, Laura C; Cortazar, Frank B; Gerber, David E; Hamad, Lamya; Hansen, Eric; Johnson, Douglas B; Lacouture, Mario E; Masters, Gregory A; et al.
Abstract : Immune checkpoint inhibitors (ICIs) are the standard of care for the treatment of several cancers. While these immunotherapies have improved patient outcomes in many clinical settings, they bring accompanying risks of toxicity, specifically immune-related adverse events (irAEs). There is a need for clear, effective guidelines for the management of irAEs during ICI treatment, motivating the Society for Immunotherapy of Cancer (SITC) to convene an expert panel to develop a clinical practice guideline. The panel discussed the recognition and management of single and combination ICI irAEs and ultimately developed evidence- and consensus-based recommendations to assist medical professionals in clinical decision-making and to improve outcomes for patients.